The Confusion of the Battlefield. A New Perspective on the Tapestries of the Battle of Pavia (c. 1525-1531) - Paredes, Cecilia (RIHA Journal, 2014)
This contribution is devoted to the tapestry cycle of the Battle of Pavia conserved at the Museo Capodimonte in Naples. Seven tapestries compose this prestigious tapestry set that commemorates the first military success of Charles V: the battle held in Pavia on 24 February 1525. Up to now the tapestries have been interpreted as independent panels representing different episodes of the battle. In this contribution we will show that the seven panels actually originated in one single design, which we rediscovered by assembling them in a different sequence. In fact, the panels provide a description of the battle in a fabulous and unique panoramic landscape: the most monumental siege city view ever conceived in the sixteenth century. This discovery not only changes our lecture of the tapestries, but also raises numerous questions that should be addressed in future studies.